Medical waste management in private medical clinics Taiping, Perak - Chua, Say Tiong; Abdul Latif, Puziah; Karuppannan, Subramaniam (Planetary Scientific Research Center, 2012)
The proper management of medical waste must be given priority and the medical waste generator has to ensure the proper medical waste management involving collection and disposal by private medical clinics with a potential disposal mixing with municipal waste stream. The study determined methods of medical waste management; and identified problems encountered and proposed measures for improvement. The study was carried out from January to October 2008 in Taiping, Malaysia; where 19 of 72 private medical clinics (n=19) (26.4%) participated in the study. Data was collected through a self-administered questionnaire survey. The analysis showed private medical clinics who disposed of medical waste with general waste (n=3) (15.8%), with inappropriate types of containers for collecting. The main problem encountered by private clinics was improper practices due to lack of awareness (n=11) (57.9%). The charges imposed by DOE registered contractor was not reasonable (n=2) (10.5%). The private medical clinics did not engage the registered contractor (n=3) (15.8%).